Cutoff interference polymer-crystalline multilayer systems with the passband edge smooth tuning - Belyaeva, A.I.; Kolomiets, S.N. (Functional Materials, 2005)
The smooth tuning possibility of the passband edge in an interference polymer-crystalline cutoff filter has been studied. This is attained by using the periodic polymer (£) — germanium (H) structures of uneven optical thickness, i.e., the systems of the [[HH±C)(L±C)k(L±C)k(H±C) type where H and L are quarter-wave layers of high and low refractive index, respectively; C in the thickness unequality parameter; k, an integer. The effect of the C value variation from 0 to 0.3 H on the optical properties of polyethylene-germanium interference structures have been studied theoretically and in experiment. A method has been developed to smooth the secondary extremes in the uneven thickness polyethylene-germanium systems by adding auxiliary polyethylene interference layers. Исследована возможность плавной перестройки границы отрезания интерференционного полимер-кристаллического фильтра. Она заключается в использовании периодических структур неравной оптической толщины, т.е. систем вида [[HH±C)(L±C)k(L±C)k(H±C), где Н и L — четвертьволновые слои с высоким и низким показателем преломления, С — параметр неравнотолщинности, к — целое число. Теоретически и экспериментально исследовано влияние изменения параметра неравнотолщинности С от 0 до 0.3 Н на оптические свойства интерференционных структур полиэтилен-германий. Разработан метод сглаживания вторичных экстремумов в системах полиэтилен-германий неравной оптической толщины добавлением дополнительных интерференционных слоев из полиэтилена. Досліджено можливість плавної перебудови границі відрізання інтерференційного полімер-кристалічного фільтра. Вона полягає у використанні періодичних структур нерівної оптичної товщини, тобто систем виду [HH±C)(L±C)k(L±C)k(H±C), де H І L — чверть-хвильові шари з високим і низьким показником заломлення, С — параметр нерівнотов-щинності, k — ціле число. Теоретично й експериментально досліджено вплив зміни параметра нерівнотовщинности С від 0 до 0.3 Н на оптичні властивості інтерференційних структур поліетилен-германій. Розроблено метод згладжування вторинних екстремумів у системах поліетилен-германій нерівної оптичної товщини додаванням додаткових інтерференційних шарів з поліетилену.